Bioactive Compounds from Zingiber Montanum and Their Pharmacological Activities with Focus on Zerumbone - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The genus Zingiber consists of about 85 species and many of these species are used as food, spices, and medicines. One of the species, Zingiber montanum (J. Koenig) Link ex A. Dietr. is native to Southeast Asia and has been extensively used as traditional medicines and food. The aim of this review was to collect and critically analyze the scientific information about the bioactive compounds and pharmacological activities of Z. montanum with focus on one of the main components, zerumbone (ZER). Various studies have reported the analysis of volatile constituents of the essential oils from Z. montanum. Similarly, many phenylbutanoids, flavonoids and terpenes were also isolated from rhizomes. These essential oils, extracts and compounds showed potent antimicrobial, anti-inflammatory and antioxidant activities among others. Zerumbone has been studied widely for its anticancer, anti-inflammatory, and other pharmacological activities. Future studies should focus on the exploration of various pharmacological activities of other compounds including phenylbutanoids and flavonoids. Bioassay guided isolation may result in the separation of other active components from the extracts. Z. montanum could be a promising source for the development of pharmaceutical products and functional foods. © 2021 Licensee MDPI, Basel, Switzerland.